In the service of science and the country. Memories of professor Aleksandra Cieślikowa - Wolnicz-Pawłowska, Ewa (1947– ) (2020)
The text is dedicated to the outstanding Polish researcher of proper names — prof. AleksandraCieślikowa, author and co-author of many significant monographs and onomasticons, which wentbeyond the limits of previous onomastic studies. The most important, selected her scientific achievementsand expert activities at the Polish Language Council and the Commission on Names ofLocalities and Physiographic Objects were presented.
280, [1] page ; 23 cm.
Keywords: Aleksandra Cieślikowa; scientific achievements; expert activities

Achievements of professor Aleksandra Cieślikowa in the field of onomastic word-formation - Biolik, Maria (Instytut Języka Polskiego Polskiej Akademii Nauk, 2020)
The article presents the achievements of professor Aleksandra Cieślikowa in the field of word-formationof proper names. The most important issues concerning the creation of anthroponyms in theOld Polish era selected from monographs and scientific articles are detailed. These issues includethe problems of motivation in onomastic word-formation, the onimization process and the way ofdescribing non-derivatized words by word formation and the participation of paradigmatic derivationin the emergence of Old Polish personal names. The views of Aleksandra Cieślikowa regardingOld Polish anthroponymy contributed to the development of onomastic word-formation, an integralpart of the grammar of proper names and gave methodological foundations for the description ofOld Polish personal names from a synchronic perspective.
280, [1] page ; 23 cm.
Keywords: Aleksandra Cieślikowa; motivation in onomastics; paradigmatic derivation; onymization; Old Polish personal names; onomastic word-formation